Análisis del perfil del turista que visita la Feria de Loja - Chuncho Gonzalez, Jeremi Fernando (2024)
The current research focuses on visitors to the Loja Fair, which year after year has a large influx of people from other cities in the country and from the city itself where it takes place. In order to know the profile of the visitors, a general objective has been established, which is to identify the profile of the tourist who visits the Loja Fair, supported by two specific objectives: “To determine the current situation of the supply and demand of the Loja Fair” and “To elaborate a plan to strengthen the tourist activity in the Loja Fair”. Regarding the first objective, a bibliographic review was conducted on the Loja Fair and the INPC methodology was used to gather information on the site under investigation, and the MINTUR file was applied to determine the hierarchy of the attraction, thus obtaining the internal analysis. In addition, the PESTEL matrix was used for an external analysis, analyzing the political, economic, social, technological, ecological and legal aspects of the attraction's environment. Information on supply and demand was gathered through interviews and surveys; based on a SWOT and a strategic SWOT, strategies were proposed for the different market segments that visit the Fair. As a result, it was determined that it is not possible to establish a single tourist profile, but that since it is an event with a greater family demand, strategies should be established by age segments that make up the family nucleus, concluding that the Fair's offer should be varied according to the segments that visit it.